Myoxanthus ortizianus (Orchidaceae), a new species from southern Colombia - Kolanowska, Marta; Szlachetko, Dariusz L. (Biodiversity: Research and Conservation, 2015)
With over 3000 species, Colombian orchid flora represents one of the richest in the World. The neotropical subtribe Pleurothallidinae is the most diverse, but it is still a poorly recognized Orchidaceae group and numerous new discoveries within national representatives are described every year. An examination of material collected recently in the Colombian department of Putumayo revealed the existence of a new species of Myoxanthus, named M. ortizianus, which is described, illustrated and placed within an identification key for national species of the nominal section of the subgenus Myoxanthus.